EXPERIMENTAL AND CFD ANALYSIS OF CO-AXIAL JET - G. Ravikumar Solomon, Balaji Ramachandran,Y. Krishna Vashista Reddy, K. Koushik Chandra, T. Gokul Nandan, M. Srisai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Jet flows are encountered in many practical applications such as jet engines, gas burners, rockets. To achieve higher spreading rates and to reduce the level of noise, different methods are employed for jet flow control, such as optimizing the shape or using acoustic liners. In this paper, the Circular and non-circular co-axial jets are compared by using flow characteristics. The non-circular shape in this study is hexagonal and cruciform. The circular and non-circular coaxial jets was made and fitted with a blower setup. The flow field characteristics such as the pressure distribution and the velocity distribution of the circular and non-circular co-axial jets were measured using a manometer and pitot tube, respectively. Decay of the jet was investigated at different axial locations quantitatively by measuring pressure in the jet field. The result of the study was validated with the help of CFD analysis using Fluent software. The Reynolds stress mathematical model is usedas governing equations for computation. It is observed that noncircular co-axial jets decay at a faster rate, and has low velocity distribution and pressure distribution compared to the circular co-axial jet. It is concluded that circular co-axial jets exhibit optimum flow characteristics compared to the non-circular co-axial jets.